Synthesis and Characterization of As-Synthesized Co-deposited PbS/ZnS Thin Films Prepared by SILAR Technique - Omoniyi, Francis O.; Omoteji, Ibrahim B.; Babalola, Olayinka A.; Imalerio, Thomas I. (Journal of Science and Technology, 2025)
Thin-film semiconductors are widely studied for their applications in various optoelectronic devices. PbS and ZnS are useful semiconductors for various optoelectronic applications, with PbS having low energy bandgap while ZnS has wide energy bandgap. In this paper, we investigate the structural, morphological, optical and electrical properties of the as-synthesized PbS/ZnS films and evaluate their potential in optoelectronic applications. PbS/ZnS thin film was synthesized using the Successive Ionic Layer Adsorption and Reaction (SILAR) method, by varying deposition cycles without post-deposition annealing. The X-ray diffraction (XRD) peaks confirmed the presence of cubic phases of PbS and ZnS with increasing crystallinity at higher SILAR cycles. Scanning electron microscopy (SEM) revealed enhanced surface coverage and grain growth with increased cycles while energy disperse X-ray spectroscopy (EDS) verified the presence of Pb, Zn and S. Optical bandgap energies ranged from 1.43 eV to 2.82 eV, which is attributed to changes in film thickness and composition. Hall Effect showed n-type conductivity with varying carrier concentration and mobility. These results highlighted the tunability of PbS/ZnS thin films via SILAR cycles, making them promising for application in solar cells and photodetectors.